Chemical composition and antibacterial activity of Pinus halepensis Miller growing in West Northern of Algeria - Fekih, Nadia (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To find new bioactive natural products, the chemical composition and to sudy the antibacterial activity of essential oil components extracted from the aerial parts of the Algerian aromatic plant Pinus halepensis Miller (P. halepensis) (needles, twigs and buds). METHODS: The essential oil used in this study was isolated by hydrodistillation using a Clevenger-type apparatus according to the European Pharmacopoeia. The chemical composition was investigated using GC-retention indices (RI) and GC-MS. RESULTS: Forty-nine compounds, representing 97.9% of the total collective oil, were identified. Essential oil was dominated by hydrocarbon compounds (80.6%) especially monoterpenes (65.5%). The major compounds from ten oils stations were: myrcene (15.2%-32.0%), α-pinene (12.2%-24.5%), E-β-caryophyllene (7.0%-17.1%), terpinolene (1.8%-13.3%), 2-phenyl ethyl isovalerate (4.8%-10.9%), terpinene-4-ol (1.0%-8.2 %) and sabinene (1.5%-6.3%). The intra-species variations of the chemical compositions of P. halepensis aerial parts essential oils from ten Algerian sample locations were investigated using statistical analysis. Essential oil samples were clustered in 2 groups by hierarchical cluster analysis, according to their chemical composition. The essential oil revealed an interesting antimicrobial effect against Lysteria monocytogenes, Enterococcus faecalis, Pseudomonas aeruginosa, Acinetobacter baumanii, Citrobacter freundii and Klebsiella pneumoniae. CONCLUSIONS: These results suggest that the essential oil from P. halepensis may be a new potential source as natural antimicrobial applied in pharmaceutical and food industries.